2021
DOI: 10.1007/s00122-021-03937-5
|View full text |Cite
|
Sign up to set email alerts
|

QTL mapping for Fusarium wilt resistance based on the whole-genome resequencing and their association with functional genes in Raphanus sativus

Abstract: Fusarium wilt is an important disease of radish, leading to severe decrease in yield and quality. In this study, we used 180 F 2 populations derived from a cross between radish inbred lines 'YR4' and 'YR18' to construct linkage group for the detecting quantitative trait locus (QTLs) related to Fusarium oxysporum resistance. Four QTLs related to Fusarium oxysporum resistance were detected on two linkage groups. Of the two major loci for FW resistance, FoRsR7.1 FOR59 was delimited to the 2.18-Mb physical interva… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 77 publications
0
0
0
Order By: Relevance
“…In the later study, Yu et al (2020) fine-mapped the Fwr1 to a region of 139.8 kb between 2 DNA markers FM82 and FM87 and identified ORF4 as a YR candidate gene that encodes a serine/arginine-rich protein kinase. In another QTL analysis of radish, Ma et al (2021) detected 2 YR-QTLs, FoRsR7.1 and FoRsR9.3 on R7 and R9 chromosomes, respectively, and further argued five putative resistance-related genes in the region of FoRsR7.1. Lee et al (2021) reported that the genome-wide association study (GWAS) analysis using 225 radish accessions identified 44 single nucleotide polymorphisms (SNPs) and twenty candidate genes associated with YR.…”
Section: Introductionmentioning
confidence: 85%
See 4 more Smart Citations
“…In the later study, Yu et al (2020) fine-mapped the Fwr1 to a region of 139.8 kb between 2 DNA markers FM82 and FM87 and identified ORF4 as a YR candidate gene that encodes a serine/arginine-rich protein kinase. In another QTL analysis of radish, Ma et al (2021) detected 2 YR-QTLs, FoRsR7.1 and FoRsR9.3 on R7 and R9 chromosomes, respectively, and further argued five putative resistance-related genes in the region of FoRsR7.1. Lee et al (2021) reported that the genome-wide association study (GWAS) analysis using 225 radish accessions identified 44 single nucleotide polymorphisms (SNPs) and twenty candidate genes associated with YR.…”
Section: Introductionmentioning
confidence: 85%
“…At approximately 10 days after germination, each F 3 plant was genotyped using ForRs1-specific DNA markers and only those having homozygous recombinant chromosomes were used for the subsequent fine-mapping study. To compare our identified ForRs1 region with the location of the candidate genes identified by Ma et al (2021), the reference genome of R. sativus cv. WK10039, Rs2.0, was used (Cho et al 2022).…”
Section: Fine Mapping Of Forrs1 Using F 2:3 Populationsmentioning
confidence: 99%
See 3 more Smart Citations